2012
DOI: 10.4085/1062-6050-47.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Frequency of Peer-Assisted Learning in the Laboratory and Collegiate Clinical Settings

Abstract: Participants perceived that students engage in unplanned PAL in the collegiate clinical setting with a stronger inclination toward engagement in peer modeling. Educators should develop planned PAL activities to capitalize on the inherent desire of the students to collaborate with their peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…With ultrasound becoming more ubiquitous in clinical practice, it is essential that medical learners, including PA students, be exposed to the technology earlier and competently trained in its use. 7 In contrast, the results of this study do not show the same effect when looking at self-efficacy and outcome expectation of workshop participation. Although both measures increased among all respondents over time, no statistically significant differences were found between workshop participants and nonparticipants.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…With ultrasound becoming more ubiquitous in clinical practice, it is essential that medical learners, including PA students, be exposed to the technology earlier and competently trained in its use. 7 In contrast, the results of this study do not show the same effect when looking at self-efficacy and outcome expectation of workshop participation. Although both measures increased among all respondents over time, no statistically significant differences were found between workshop participants and nonparticipants.…”
Section: Discussioncontrasting
confidence: 84%
“…6 This style of education is a multifaceted, learner-centered model that encourages social interactions to benefit both students and teachers. 7 Social cognitive theory (SCT) is a promising framework to study POCUS education while using PAL. According to SCT, a person will not perform a behavior unless (1) that person believes he or she has the ability and skill to perform the behavior (self-efficacy), and (2) performing the behavior will result in a valued outcome (outcome expectations).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have explored both forms. For example, a recent study by Henning et al 2012 [4] found that athletic training students engaged in more PAL activities that were unplanned, rather than planned [4] . Several other papers have recommended that planned PAL be integrated into the curriculum [5][6][7][8][9] .…”
mentioning
confidence: 99%
“…Thus, further education on optimally facilitating a PL approach along with clearer transparency on the evolution of the model to support student autonomy as the year progressed were identified as common concerns. The current literature identifies that preceptors may not feel adequately supported to facilitate PL [5, 16], reporting the need to develop organizational skills, feedback skills, and strategies to cope with the dual role of patient care provider and educator [2, 5, 17]. The preceptors in our study reported varying levels of preparedness, identifying that further education on how to effectively support PL using a 2:1 model should be forefront in subsequent clinical years.…”
Section: Resultsmentioning
confidence: 86%